Steel Brace Connection with Reinforced Concrete Frame Structure: A Review - Bohara, Birendra Kumar (Marasofi International Media and Publishing (MIMP), 2025)
Steel bracing is widely used in reinforced concrete (RC) structures to enhance their lateral load resistance and seismic performance. This review paper compiles and examines various experimental and numerical studies on steel bracing systems and their connection details with RC frames. Three primary types of brace-to-frame connections were analysed, focusing on their effects on structural parameters such as crack patterns, response modification factor (R factor), overstrength, and stiffness. The studies show that while the X-bracing configuration has been extensively examined, other bracing types require further investigation, particularly regarding their connection behaviour and performance. Observations highlight that bracing significantly reduces inter-story drift, displacement, and natural period while increasing base shear capacity. However, the effectiveness of the bracing system largely depends on the type and strength of the connection between the steel braces and RC elements. Issues such as hinge formation near brace connections, shifting of plastic hinges, and localized failures in beams and columns demand further exploration. Additionally, experimental studies reveal that inadequate connections can lead to premature failure, while well-designed connections improve strength, energy dissipation, and ductility. This review emphasizes the urgent need for developing standardized, simple, and effective connection detailing for both new construction and retrofitting purposes. Future research should focus on optimizing the design of brace connections in various configurations, quantifying overstrength factors and stiffness ratios, and extending the study to diverse bracing types beyond the commonly studied X-bracing.